2013
DOI: 10.1111/bld.12053
|View full text |Cite
|
Sign up to set email alerts
|

‘Happy and a bit Nervous’: the experiences of children with autism in physical education

Abstract: Accessible summary• Twelve children with autistic disorder (aged 9-13 years) talked about their time in physical education.• The children spoke about good and bad experiences they had in physical education. • Most of the children found some activities hard to do and felt left out at times. • They enjoyed spending time with other children and making friends. SummaryTwelve students with autistic disorder participated in interviews to reveal their perspective of physical education. Inductive thematic analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 37 publications
2
95
0
3
Order By: Relevance
“…Meaningful learning experiences for students with disabilities in PE are extensively dependent on teachers' skills to and attitudes toward communicating and structuring their teaching in an inclusive direction (Jordan, Glenn, and McGhie-Richmond 2010). Participation restriction may be experienced if the activity is not adapted to students in need of special support (Smith 2004;Coates and Vickerman 2010;Healy, Msetfi, and Gallagher 2013). Students with physical disabilities describe good days in PE as lessons in which they experience a sense of belonging, their participation as skillful and where you share benefits (Goodwin and Watkinson 2000).…”
Section: Disability and Perceived Participation In Pementioning
confidence: 99%
“…Meaningful learning experiences for students with disabilities in PE are extensively dependent on teachers' skills to and attitudes toward communicating and structuring their teaching in an inclusive direction (Jordan, Glenn, and McGhie-Richmond 2010). Participation restriction may be experienced if the activity is not adapted to students in need of special support (Smith 2004;Coates and Vickerman 2010;Healy, Msetfi, and Gallagher 2013). Students with physical disabilities describe good days in PE as lessons in which they experience a sense of belonging, their participation as skillful and where you share benefits (Goodwin and Watkinson 2000).…”
Section: Disability and Perceived Participation In Pementioning
confidence: 99%
“…Bullying against children with ASD in physical education settings were also reported in the literature (Garcia Biggs, Simpson, & Gaus, 2010;Healy, Msetfi, [ 1 6 _ T D $ D I F F ] & Gallagher, 2013). Specifically, Healy et al (2013) reported that besides, psychological bullying, children with ASD in their study experienced physical bullying in physical education settings which isolated children with ASD to actively participate in physical education. This was also echoed in quotes by mothers from families 1, 5, and 6 in this study.…”
Section: Understanding Pa In Children With Hfasdmentioning
confidence: 99%
“…PA settings were being avoided as a measure to prevent injury as a result of these safety concerns. From a programmatic standpoint, the notion of training, attitude facilitation of teachers, and other factors are needed to help a child with HFASD participate safely with peers in PA (Garcia Biggs et al, 2010;Healy et al, 2013). A concerning phenomenon emerged in these data that some children with HFASD are oblivious to inherent risks associated with PE and recreational activities.…”
Section: Understanding Pa In Children With Hfasdmentioning
confidence: 99%
“…Another individual describes skipping and dropping university classes because of sensory reactions to the sound of an instructor's voice and to the smells of chemicals (p. 50) [6]. Numerous qualitative studies also make note of sensory symptoms (e.g., [7][8][9][10]). These qualitative and autobiographical accounts of differential sensory processing in ASD are supported by a growing number of empirical studies.…”
Section: Introductionmentioning
confidence: 99%